О ДВУСТОРОННИХ ПРИБЛИЖЕНИЯХ К ПЕРИОДИЧЕСКИМ РЕШЕНИЯМ ИНТЕГРО-ДИФФЕРЕНЦИАЛЬНЫХ УРАВНЕНИЙ ТИПА ФРЕДГОЛЬМА - Нуржанов, О.Д.; Айназаров, К.А. (SCIENCE and SOCIETY, 2022)
In this paper, the method of two-sided approximations is applied to the study of periodic solutions of integro-differential equations of the Fredholm type.